2018
DOI: 10.1177/0961203317753069
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus infection and type I interferon signature in patients with systemic lupus erythematosus

Abstract: Epstein-Barr (EB) virus infection has long been speculated to evoke systemic lupus erythematosus (SLE). Since a virus infection can induce interferon (IFN) system activation, we aimed to discover the relationship between the two in the progression of SLE in a Chinese inpatient cohort. Methods Peripheral blood mononuclear cells and sera were isolated from 116 SLE patients and 76 healthy controls. Antibodies against EBV-VCA (IgM and IgG) and EBNA (IgG) along with IFNα in patient sera were detected with enzyme-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
(40 reference statements)
4
20
0
Order By: Relevance
“…Compared to the results of previous studies, unexpectedly, we did not detect HFV, HHV6, and HTLV in PBMCs of SLE patients. We also did not detect HHV8 (Naganuma et al, 2008;Broccolo et al, 2013), but EBV (Han et al, 2018) and HHV5 (Chen et al, 2015) were detected in PBMCs of SLE patients, as in previous studies. In addition, the diagnostic capabilities of two viruses, namely HHV5 and HHV8 (screened by Random Forests-based backward feature selection; Figure 2A), which might serve as SLE markers, were selected and discussed in this study based on previously published data.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Compared to the results of previous studies, unexpectedly, we did not detect HFV, HHV6, and HTLV in PBMCs of SLE patients. We also did not detect HHV8 (Naganuma et al, 2008;Broccolo et al, 2013), but EBV (Han et al, 2018) and HHV5 (Chen et al, 2015) were detected in PBMCs of SLE patients, as in previous studies. In addition, the diagnostic capabilities of two viruses, namely HHV5 and HHV8 (screened by Random Forests-based backward feature selection; Figure 2A), which might serve as SLE markers, were selected and discussed in this study based on previously published data.…”
Section: Discussionsupporting
confidence: 72%
“…Previous research showed that many viruses are present in PBMCs. Human foamy virus (HFV) (Sun et al, 2006), Epstein-Barr virus (EBV) (Han et al, 2018), human T lymphotropic virus type I (HTLV) (Akimoto et al, 2007), human cytomegalovirus (HCMV) (Chen et al, 2015), and human herpesvirus 6 (HHV6) (Broccolo et al, 2013) exist in PBMCs or peripheral blood leukocytes of SLE patients. Although some viruses have been detected in PBMCs of SLE, virome diversity and variations in the PBMC microbial flora remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…A collection of genes associated with inflammation, interferon I and II activity in addition to neutrophil and macrophage deregulators were also differentially expressed between EBV positive and negative samples. These genes include MX1, ANAX2P2, DEFA1, NCF1C, CLC, and SPIB 2427 . GO biological enrichment analysis found enrichments including an increase in reactive oxygen species and metabolic cell processing pathways when the tumor samples were classified as EBV positive (ROS metabolic process).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, it was observed that EB virus loads are significantly higher in patients with active SLE . The patients with SLE had higher rate of latent membrane protein 1 (LMP1) expression, which was positively correlated with the IFN‐stimulated genes . Latent membrane protein 1 (LMP1) of EBV was observed to induce autophagy.…”
Section: Sle and Links With The Environmentmentioning
confidence: 99%